AKIBAT HUKUM ATAS PERJANJIAN JUAL BELI TANAH DENGAN HAK MEMBELI KEMBALI (Studi Putusan No. 38/Pdt.G/2019/PN.Bdw) - Diandra Alifa Risha; Rafiqi Rafiqi; Arie Kartika (ARBITER: Jurnal Ilmiah Magister Hukum, 2022)
The sale and purchase agremeent with the right to repurchase is the power to the buy back goods that have been sold a rising from an agremeent which the seller is given the right to take back the goods he sells, by returning the original purchase price accompained by compensation in the form of costs incurred to carry out the purchase, as well as costs for carrying out the purchase make corrections (Article 1519 KUHPerd). Land is object of research in the form of immovable objects. The problems in this study are the legal consequences of the sale and purchase agreement of land with the right to buy back, the judge’s considerations are related (Verdict Studies Number 38/Pdt.G/2019/PN.Bdw).The research is a normative juridical law researcch, positive law that leads to normative legal research, using secondary data sources obtained from statutory regulations and literature materials related to me object of the research problem. The results show that the legal consuquences of buying and selling land with the right buy back are the seller hs the right buy back goods he sells because of an agreement to return the money to the buyer as a replacement money as a reffered to (Article 1532 KUHPerd). Meanwhile the judge’s considerations regarding the sale and purchase of has complied with the provisons of the applicable laws and regulations.